2016
DOI: 10.1016/j.joms.2016.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Morbidity and Mortality Rates After Maxillomandibular Advancement for Treatment of Obstructive Sleep Apnea

Abstract: Purpose To compare morbidity and mortality rates in obstructive sleep apnea (OSA) versus dentofacial deformity (DFD) patients undergoing equivalent maxillofacial surgical procedures. Patients and Methods Patients with OSA who underwent maxillomandibular advancement with genial advancement (MMA), at Massachusetts General Hospital Department of Oral and Maxillofacial Surgery, from December 2002 to June 2011, were matched to patients with DFD undergoing similar maxillofacial procedures during the same time peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 41 publications
(40 reference statements)
2
21
0
Order By: Relevance
“…Our study is in agreement with Passeri et al 45 that older DFD patients ($30 years) scheduled to undergo bimaxillary orthognathic surgery are more likely to have symptomatic OSA than younger patients (<30 years). This is not unexpected because weight gain and pharyngeal muscle relaxation tend to occur with age, adding risk for OSA.…”
Section: Discussionsupporting
confidence: 93%
“…Our study is in agreement with Passeri et al 45 that older DFD patients ($30 years) scheduled to undergo bimaxillary orthognathic surgery are more likely to have symptomatic OSA than younger patients (<30 years). This is not unexpected because weight gain and pharyngeal muscle relaxation tend to occur with age, adding risk for OSA.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, the authors listed the major complication rate at 13.9%, using major complications as the numerator and total complications as the denominator. Fifteen major complications in 28 patients is a 53.5% major complication rate, most of which were infections per the authors [12].…”
Section: Facial Bone Expansion Strategiesmentioning
confidence: 79%
“…76 However, a retrospective case-control study found that 13.9% of patients had a major complication that required repeat admission or unplanned surgery after maxillomandibular advancement, and numerous minor complications can occur. 77 Regular follow-up to assess for recurrence of OSA is recommended. 75 Laser-assisted uvuloplasty or uvulopalatopharyngoplasty are unreliable for reducing the AHI or improving patient outcomes, and are not recommended.…”
Section: Alternative Treatmentsmentioning
confidence: 99%